(untitled) (مجلة ديالى للبحوث الانسانية, 2023)
Abstract The aim and capabilities of assessment have expanded in modern educational systems, and teachers are required to be well-versed in the fundamentals of contemporary assessment. In light of this, the current study examined the Language Assessment Test Literacy of English language teachers of Iraq using the Classroom Assessment Literacy Inventory (CALI), which was developed using the American Federation of Teachers, National Council on Measurement in Education’s, and National Education Association’s seven standards of teachers’ Language Assessment Test Literacy expertise for the instructional assessment of students. The data has been collected using the qualitative and quantitative methodology. The results showed that out of 35 questions, Iraq’s English language teachers only provided less than 15 right answers. Findings show that standard seven scores for instructors were the lowest. The standard four students received the highest grade. Despite the fact that 77% of teachers claimed to have had enough assessment training, the findings showed that they had small amounts of assessment literacy. It is advised that teacher preparation programs be revised and that in-service teachers be given professional development courses.